HLA-BAT1 alters migration, invasion and pro-inflammatory cytokines in prostate cancer - García-Vargas, Aileen M.; Roque-Reyes, Yarelis M.; Arroyo-Villegas, Desiree M.; Santiago-Negron, Daniel; Sánchez-Vázquez, María M.; Rivera-Torres, Alejandro; Reyes-Meléndez, Andrea C.; Cardona-Berdecía, Valerie; García-Maldonado, Miosotis; Víquez, Olga M.; Martínez-Ferrer, Magaly (Frontiers in Oncology, 2022)
Prostate cancer (PCa) accounts for more than 1 in 5 diagnoses and is the second cause of cancer related deaths in men. Although PCa may be successfully treated, patients may undergo cancer recurrence and there is a need for new biomarkers to improve prediction of prostate cancer recurrence and improve treatment. Our laboratory demonstrated that HLA-B associated transcript 1 (BAT1) was differentially expressed in patients with high Gleason scores when compared to low Gleason scores. BAT1 is an anti-inflammatory gene but its role in PCa has not been identified. The objective of this study is to understand the role of BAT1 in prostate cancer. In vitro studies showed that BAT1 down-regulation increased cell migration and invasion. In contrast, BAT1 overexpression decreased cell migration and invasion. RT-PCR analysis showed differential expression of pro-inflammatory cytokines (TNF-α and IL-6) and cell adhesion and migration genes (MMP10, MMP13 and TIMPs) in BAT1 overexpressed cells when compared to BAT1 siRNA cells. Our in vivo studies demonstrated up-regulation of TNF-α, IL-6 and MMP10 in tumors developed from transfected BAT1 shRNA cells when compared to tumors developed from BAT1 cDNA cells. These findings indicate that BAT1 down-regulation modulates TNF-α and IL-6 expression and promotes migration and invasion through MMP and TIMP expression.